Biological characterization of purified macrophage-derived neutrophil chemotactic factor - M. Dias-Baruffi; M. C. Roque-Barreira; F. Q. Cunha; S. H. Ferreira (Mediators of Inflammation)
We have recently described the purification of a 54 kDa acidic protein, identified as macrophage-derived neutrophil chemotactic factor (MNCF). This protein causes in vitro chemotaxis as well as in vivo neutrophil migration even in animals treated with dexamethasone. This in vivo chemotactic activity of MNCF in animals pretreated with dexamethasone is an uncommon characteristic which discriminates MNCF from known chemotactic cytokines. MNCF is released in the supernatant by macrophage monolayers stimulated with lipopolysaccharide (LPS). In the present study, we describe some biological characteristics of homogenous purified MNCF. When assayed in vitro, MNCF gave a bell-shaped dose–response curve. This in vitro activity was shown to be caused by haptotaxis. Unlike N-formyl-methionylleucyl- phenylalanine (FMLP) or interleukin 8 (IL-8), the chemotactic activity of MNCF in vivo and in vitro, was inhibited by preincubation with D-galactose but not with D-mannose. In contrast with IL-8, MNCF did not bind to heparin and antiserum against IL-8 was ineffective in inhibiting its chemotactic activity. These data indicate that MNCF induces neutrophil migration through a carbohydrate recognition property, but by a mechanism different from that of the known chemokines. It is suggested that MNCF may be an important mediator in the recruitment of neutrophils via the formation of a substrate bound chemotactic gradient (haptotaxis) in the inflamed tissues.